Heteroscedastic Conditional Auto-Regression Models for Areally Referenced Temporal Processes for Analysing California Asthma Hospitalization Data. Issue 5 (30th April 2015) - Quick, Harrison; Carlin, Bradley P.; Banerjee, Sudipto
Summary: Often in regionally aggregated spatiotemporal models, a single variance parameter is used to capture variability in the spatial structure of the model, ignoring the effect that spatially varying factors may have on the variability in the underlying process. We extend existing methodologies to allow for region-specific variance components in our analysis of monthly asthma hospitalization rates in California counties, introducing a heteroscedastic conditional auto-regression model that can greatly improve the fit of our spatiotemporal process. After demonstrating the effectiveness of our new model via simulation, we reanalyse the asthma hospitalization data and note some important findings.